2007
DOI: 10.1111/j.1532-849x.2007.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Dual‐Cured Resin Luting Agents for Ceramic Restoration

Abstract: Three-point bending tests were performed after 24 h storage at 37°C. Two different-shaped zirconia ceramic specimens with or without sandblasting with alumina were treated with each primer. The specimens were then cemented together with each resin luting agent. Half of the specimens were stored in water at 37°C for 24 h and the other half were thermocycled 5,000 times. Results: VLII revealed statistically higher Knoop hardness and flexural modulus than NRC for each thickness of ceramic. No significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
3
23
0
3
Order By: Relevance
“…Previous studies corroborate that dualcured luting agents are dependent on adequate light exposure to achieve higher conversion 8,26 and generate better properties. [9][10] Furthermore, it has been suggested that delayed light activation could improve the degree of conversion, mainly when the energy dose applied over the material is low. 27 The indirect light activation used in the current study reduces the energy dose, 26 but no effects of delayed activation were observed in bond strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies corroborate that dualcured luting agents are dependent on adequate light exposure to achieve higher conversion 8,26 and generate better properties. [9][10] Furthermore, it has been suggested that delayed light activation could improve the degree of conversion, mainly when the energy dose applied over the material is low. 27 The indirect light activation used in the current study reduces the energy dose, 26 but no effects of delayed activation were observed in bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the polymerization of dual-polymerized resin cements might depend on their exposure to light for achieving better mechanical properties. [9][10] Despite the importance of proper polymerization of resin cements with regards to the retention of indirect restorations, bond strength evaluations are conventionally performed at 24 hours or longer after restorative procedures. [11][12][13] Clinically, however, the interfaces are subjected to stress immediately upon completion of cementation.…”
Section: Introductionmentioning
confidence: 99%
“…18 The use of definitive cements may complicate the ability to retrieve implant-supported superstructures, whilst temporary materials invite premature loosening. 19,20 Permanent cements, such as zinc phosphate or glassionomer, are being replaced by universal dual-cure MDP (methacryloxy-decyl-dihydrogen phosphate)-based 21 and self-adhesive resin agents 22 in order to improve the cement stability, retention, and resistance. 23 However, their suitability for implant restorations is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Cementation is an important factor for vertical fit because it may prevent complete seating of the restoration due to intracoronal pressure 25) . The suitability of permanent luting materials, such as zinc phosphate or glass-ionomer universal dual-cure methacryloxy-decyl- dihydrogen phosphate-based and self-adhesive resin cements, deserves further investigation 26,27) . The purpose of this study was to evaluate the marginal adaptation of five ceramic systems fabricated using different techniques on implant abutments with different finish lines.…”
Section: Introductionmentioning
confidence: 99%